Association of Vesicoureteric Reflux (VUR) in Children with Symptomatic Urinary Tract Infection (UTI) - in a Tertiary Care Hospital, Dhaka, Bangladesh (Bangladesh Journal of Child Health, 2013)
Background: Vesicoureteric reflux is the most common urinary tract anomaly affecting the children which predisposes to higher rates of urinary tract infection and renal scarring than those without VUR. Objective: To find out the associations of VUR in children presented with UTI. Methodology: This cross sectional study was conducted in 36 children aged 1 month to 16 years who were admitted due to UTI in the Pediatric Nephrology Department of Bangabandhu Sheikh Mujib Medical University (BSMMU) from July 2009 to June 2010. UTI were evaluated by urinalysis, culture and sensitivity test, ultrasonography of the urinary system with post-voidal residue and micturating cystourethrogram subsequently. Results: This study revealed that UTI were most frequent in boys (P